POLITIK HUKUM PEMBENTUKAN DEWAN PENGAWAS DIKAITKAN DENGAN INDEPENDENSI KEWENANGAN YUDISIAL KOMISI PEMBERANTASAN KORUPSI - Gabby Vionalisyah; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This study aims to find out how legal politics related to the formation of a supevisory board is associated with the independence of the judicial authority of the corruption eradication commission. The formulation of the problem raised is how the Judicial Eradication Commission’s judicial authority arrangements after the decision of the Constitutional Court and how the legal politics of establishing a supervisory board is related to the independence of the Corruption Eradication Commission’s judicial authority.This research is a normative juridical research, research conducted based on legal material and legislation. The approach taken includes the literature approach, namely by studying books and legislation. The type of data used is the type of premier data, namely the source of data obtained through laws related to the Corruption Eradication Commission’s, secondary data sources namely data sources originating from books and other regulations, consisting of premier legal material, statutory regulation governing the Corruption Eradication Commission’s.The theories used in this research are the theory of state institutions and legal political theory. The results of this study indicate that after the enactment of Law Number 19 of 2019 concerning the second Amendment to Law Numbe 30 of 2002. Concerning Corruption Eradication Commission’s (KPK), the position of the KPK which was originally a non-governmental institution is now included in the executive power cluster, and the existence of the addition of articles in Law Number 19 of 2019 related to the exsistence of a Board of Trustees contained in Article 12B and Article 12C. With the addition of Article concerning the Supervisory Board, the KPK in carrying out its duties and authority is no longer independent and weakens the independence of the KPK.Whereas in the Constitutional Court Decision Number 36/PUU-XV/2017 states, “That the KPK can be object of the DPR’s questionnaire rights in its oversight function, the DPR can exercise its constitutional rights including the inquiry right to the KPK only limited to matters relating to implementation of the duties and authority of the KPK in addition to carrying out the duties and authorities relating to its judicial duties and authorities (investigation, investigation and prosecution)”. This makes no synchronization between the decision of the Constitutional Court Number 36/PUU-XV/2017 with law number 19 of 2019 concerning the Corruption Eradication CommissionKeywords: the authority of the corruption eradication commission, the ruling of the constitutional court, amendments to the law